Prevalence and Therapeutic Efficacy of Anthelmintic against Neoascaris vitulorum in Buffalo Populations from Sylhet District of Bangladesh - Kanu, Shishir; Chowdhury, Md. Shahidur Rahman; Sabur, Md. Abdus; Rahman, Md. Mahfujur; Islam, Kazi Mehetazul; Uddn, Md Bashir; lslam, Md. Rafqul; Hossain, Md. Mukter (Journal of Buffalo Science, 2021)
Background and Objectives: The epidemiological features of Neoascaris vitulorum infection in buffaloes are important to know their transmission and risk factors assessment as well treatment regimens. This study was conducted with the objectives of determining the prevalence of Neoascaris vitulorum infection in buffaloes in Sylhet district of Bangladesh and to evaluate the efficacy of anthelmintics against the parasite. Materials and Method: A total of 211 fecal samples were collected from buffaloes and examined for the detection of parasitic eggs during the period from July 2017 to June 2018. For the determination of therapeutic efficacy, animals were randomly divided into 6 groups (T0, Ti, T1, T2, T3, T4) where each group consisting of 3 buffaloes. The group T0 (negative control-non infected) and Ti (positive control-infected) were treated only with phosphate buffer saline (PBS). The other four infected groups were treated as T1 with albendazole, T2 with piperazine citrate, T3 with ivermectin and T4 with combination of tetramisole HCL and oxyclosanide. Before trials day 0 and after treatment of 7th, 14th, 21st and 28th days fecal samples examined using McMaster technique. Results: The overall prevalence was estimated 17.06% (36/211). The prevalence was higher among buffalo calves of below six months (39.28%) followed by 6 months to 1 year, 1 to 2 years and above 2 years as 25%, 22.5% and 7.20% respectively. The infection rate was high in females (20.0%) than males (13.18%). The parasite was more prevalent in rainy (21.42%) than summer (16.67%) and winter (14.29%) seasons. The EPG results revealed piperazine citrate was the most effective (100%) against Neoascaris vitulorum. The percent efficacies of other anthelmintic used in this study were albendazole, ivermectin and combination of tetramisole HCL and oxyclozanide as 95.49%, 86.20% and 95.58% respectively. Conclusion: The prevalence of Neoascaris vitulorum infection in buffalo at Sylhet district of Bangladesh was relatively high. The results revealed that piperazine citrate, tetramisole HCL and oxyclozanide combination are highly effective for the reduction of egg per gram (EPG) of Neoascaris vitulorum infection in buffalo. On the other hand ivermectin and albendazole were also around ninety percent effective respectively.